2015
DOI: 10.1007/s40801-015-0033-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hospitalization on Antihypertensive Pharmacotherapy among Older Persons

Abstract: BackgroundLittle is known about the impact of hospitalization on antihypertensive pharmacotherapy and blood pressure control in older persons.ObjectivesThe aim of this study was to explore the impact of hospitalization on the management of hypertension and antihypertensive pharmacotherapy in a cohort of older patients with a documented diagnosis of hypertension.MethodsA retrospective, cross-sectional medical record audit was conducted in a large Australian metropolitan teaching hospital. Patients aged 65 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…However the importance of understanding blood pressure control in older persons presenting to hospital should not be underestimated. Previous work in the same cohort found that 70% of the cohort was not at target BP prior to hospitalization (Alhawassi et al, 2015). The same research reported that hospitalization was associated with considerable change to antihypertensive medication regimens, even when the primary reason for admission is non-cardiovascular (Alhawassi et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However the importance of understanding blood pressure control in older persons presenting to hospital should not be underestimated. Previous work in the same cohort found that 70% of the cohort was not at target BP prior to hospitalization (Alhawassi et al, 2015). The same research reported that hospitalization was associated with considerable change to antihypertensive medication regimens, even when the primary reason for admission is non-cardiovascular (Alhawassi et al, 2015).…”
Section: Discussionmentioning
confidence: 93%
“…Previous work in the same cohort found that 70% of the cohort was not at target BP prior to hospitalization (Alhawassi et al, 2015). The same research reported that hospitalization was associated with considerable change to antihypertensive medication regimens, even when the primary reason for admission is non-cardiovascular (Alhawassi et al, 2015). Finally, data extraction was undertaken by a single researcher to ensure consistency throughout the study but, common to all retrospective studies reliant on health record data, data quality and availability was dependent on the quality of documentation by the health care team at the time of care.…”
Section: Discussionmentioning
confidence: 93%
“…It is well established that a comprehensive evaluation performed during hospitalization and the resulting drug treatment revision and reconciliation have a great impact on clinical outcomes in older patients. Indeed, previous reports identified hospitalization as a major factor that induced antihypertensive treatment modifications or discontinuation mainly due to adverse reactions 22,23 . Therefore, the correct management of any pharmacological therapy should be a balance between the correct prescription and the avoidance of adverse effects, and this seems to be particularly important in older subjects during in‐hospital stay and pharmacological reconciliation process.…”
Section: Discussionmentioning
confidence: 99%